KELEMANTAN DENGAN TIPE T-GIRDER BERDASARKAN SNI 1725-2016 - S, Zulfani; Alamsyah, Alamsyah; Puhululawa, Indriyani (Politeknik Negeri Bengkalis, 2023)
Bridge road river two Kelemantan with a length of 24 m and a width of 5.14 m. connects the village of Kelemantan to Sungai Dua Village, Kelemantan, Bengkalis sub-district. That this bridge was built several years ago may still use the old SNI imposition. Over time, the loading standard for RSNI T02-2005 bridges has been updated to become SNI 1725:2016. For the planning of the bridge in Sungai Dua Kelemetan Village, this has referred to SNI 1725-2016 concerning loading for bridges and SNI T-12-2004 regarding planning of concrete structures for bridges. Based on the planning results obtained negative and positive reinforcement slab D16-100 mm and reinforcement for D13-100 mm. For curb reinforcement D16-200 mm and longitudinal reinforcement D13-200 mm. The girder beam reinforcement for bending reinforcement is obtained 18D32 mm and 5D32 compression reinforcement. Meanwhile, the shear reinforcement is Ø13-100 mm and the web reinforcement is 8Ø13 mm. Reinforcement for diaphragm beams using 3D16 mm and shear reinforcement obtained Ø13-150 mm and shrinkage reinforcement obtained 2Ø13 mm. For longitudinal and transverse reinforcement plates obtained D16-200 mm. Calculation of reinforcement by Barbending Schedule with the need for plain U 24 steel of 3278.81 Kg and U 32 uilr of 21518.80 Kg. Implementation of this bridge requires a fee of Rp. 1.304.840.000,00